BLOOD GLUCOSE LEVEL AND ORGANOLEPTIC EVALUATION OF THE NATIVE AND UPGRADED NATIVE CHICKEN - Bejar, Feleciano R.; Baylon, Manuel J.; Paldez, Romeo N.; Bejar, Elvie T.; R. Aquino, Reynaldo (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The study focused on the evaluation of the Blood glucose and organolepticattributes of the progeny of Kabir and native chicken as well as progeny of nativeand native chicken. The parameters included in this study were; live and carcassweight, dressing percentage,giblets weight, weights of meat cuts, skin and flesh color acceptability, desirability,intensity, texture, tenderness, juiciness, general acceptability.Results showed that live and dressed weights between the two F1 crossesboth fasted and non-fasted showed significantly different, with kabir-native crossshowed higher or heavier weights. The result has an economic bearing the fact thatfasting before dressing the chicken can be practiced without compromising thedressing percentage. The results on meat cuts, data showed significantly higher forkabir-native F1 cross, except for the weights of heart, wings, head and neck, andfeet which showed no significant difference between the two F1 crosses.Data on skin color did not vary significantly between the two groups ofprogenies. Flesh color of the meat between the two groups differ significantly withnative-native cross significantly higher than the kabir-native cross. Acceptability ofthe carcass color is significantly higher for the kabir-native F1 considering its colorcombination of pale pink with yellow tinge color which probably contributedattraction to the meat The general acceptability results for the two groups of meat ranges from3.23±0.92 to 3.85±1.15. The Native-native F1 meat samples had significantly higherthan the kabir-native F1 meat samples. The relatively higher sensory scores fornative-native F1 meat except on intensity and tenderness could have contributed tothe overall appraisal of the meat.